Rehabilitation and Reconstruction of the North-East: The Role of Sukuk Financing - Abubakar, Adam Muhammad; Lawa, Nuraddeen Mohammed (IKONOMIKA, 2020)
The Northeast region of Nigeria has been experiencing the devastating impact of Boko Haram insurgencysince 2009, which triggeredhumanitarian crisis and destruction of infrastructure,such as schools, hospitals, roads, bridges as well as homes and farmlands, leading to many becoming internally displaced persons and refugees. Both governmental and non-governmental organizations have been mostly providing relief services and materials, whilst only few Federal Government agencies and State Governmentsare providing reconstruction and rehabilitation due to insufficient sources of funds(Olaseni, 2012).The emergence of Sukuk to Nigerian Capital Market is a new development that provides alternative funding avenue for both State and Federal Governments to finance projects and infrastructure development for nation building (Alaro, 2020).It is against this backdrop that this study aims to reviewthe approaches of financing rehabilitation and reconstruction programmes in the Northeast and examines how the potentials ofSukuk financing could properly be utilized to complement the infrastructural deficit in the region. Thus, the research is an exploratory qualitative research that sourced cross sectional primary data collected through the use of structured questionnaire. Multistage purposive sampling method was employed in selecting the respondents for the study across the study area. Thematic Analysis was employed as the method of data analysis. Both descriptive and inferential statistics were used to summarize and interpret the results of the thematic analyses of the data obtained.Keywords: North-East, Reconstruction, Rehabilitation and Sukuk Financing